Sequence analysis and evolutionary perspectives of ROB-1 beta-lactamase. - Juteau, J M (1990)
The nucleotide sequence of the ROB-1 beta-lactamase gene from Haemophilus influenzae plasmid RRob was determined. The structural gene encodes a polypeptide of 305 amino acids, with an estimated molecular mass of 30,424 for the mature form of the protein. The ROB-1 gene showed low homologies with other beta-lactamases at the nucleic acid level. By using two statistical computer methods, assessment of the extent of similarity between ROB-1 and other known beta-lactamase amino acid sequences suggested that ROB-1 is a class A enzyme. Alignment of class A beta-lactamases with ROB-1 identified conserved residues. The use of a mutation matrix for detecting distance relationships indicated that ROB-1 has higher values and homologies with beta-lactamases of gram-positive bacteria, giving insight into its ancestry and divergence.